Strategic analytics : insights you need from Harvard Business Review. (Boston, Massachusetts : Harvard Business Review Press, 2020)
Is your data strategy ready for the next wave of analytics? Data analytics offer an incredible opportunity to predict the future, engage with new technological advancements, and gain valuable insights about your business. But unless you're staying on top of the cutting edge of analytics, your company is wasting that potential--and your competitors will be gaining speed while you fall behind. These articles by experts and consultants will help you understand today's essential thinking about what data analytics are capable of now, how they will evolve, and how to adopt their use in your organization. Strategic Analytics: The Insights You Need from Harvard Business Review will help you kick off urgent conversations, focus on the right initiatives in your company, and capitalize on the opportunity of analytics.
Introduction : What makes analytics strategic : they make your strategy or business model possible / by Thomas H. Davenport -- The five essential elements for succeeding with data : and the costs of missing any / by Thomas C. Redman -- Understanding the types of data and how they're captured : increase your data literacy / by Hugo Bowne-Anderson -- The right way to deploy predictive analytics : focus first on your team, then on technology / by Eric Siegel -- What great data analysts do : and why every organization needs them / by Cassie Kozyrkov -- What data is and isn't good for : numbers rarely reveal the "why" / by Joel Shapiro -- Prioritize which data skills your company needs : consider time versus utility / by Chris Littlewood -- How a German manufacturing company set up its analytics lab : best practices any company can follow / by Niklas Goby, Tobias Brandt, and Dirk Neumann -- Cloud computing is helping smaller, newer firms compete : renting computing power may level the playing field / by Nicholas Bloom and Nicola Pierri -- Data science and the art of persuasion : solving data's last-mile problem / by Scott Berinato -- How Vineyard Vines uses analytics to win over customers : by integrating behavioral data and predictive algorithms / by Dave Sutton -- How to use employee data responsibly : three ways to maintain trust when using people analytics / by Ellyn Shook, Eva Sage-Gavin, and Susan Cantrell -- What AI-driven decision making looks like : sometimes, humans need to get out of the way / by Eric Colson -- How companies can use the data they collect to further the public good : and why they benefit from doing so / by Edward L. Glaeser, Hyunjin Kim, and Michael Luca.
Includes index.
Keywords: BUSINESS PLANNING